Education and the UN Sustainable Development Goals : praxis within and beyond the classroom / Kim Beasy, Caroline Smith, Jane Watson, editors. - Beasy, Kim; Smith, Caroline; Watson, Jane (Jane M.) (Education for sustainability ;, 2023)
This volume focuses on the complex relationship between education and the Sustainable Development Goals (SDGs) and highlights how important context is for both critiquing and achieving the Goals though education, given the critical role teachers, schools and curriculum play in young people's lives. Readers will find examples of thinking and practice across the spectrum of education and training sectors, both formal and informal.